- Identifikasi daun Ceguk dengan Spektroskopi UV-VIS - Samsul Hadi (Jurnal Kimia Fullerene, 2022)
Ceguk have two different varieties seen in the shape of the flowers, some are elongated and rounded. Based on this varietal difference, it is likely that it will affect the activity produced by the leaves. The purpose of this study was to identify the typical spectra of these two varieties using a finger print approach using UV-vis combined multivariate spectroscopy. The results of the PLSR Combretum indicum Varr analysis. B against Combretum indicum Varr. M at a wavelength of 248.53-221.00 nm, the second derivative obtained an RMSEC value of 1.65; R2 0.9988; RMSEP 5.05; R2 0.9925, and RMSECV 8; R2 0.9804. While at a wavelength of 296.09-261.64 nm, the normal model obtained an RMSEC value of 0.647; R2 0.9998; RMSEP 0.868; R2 0.9997, and RMSECV 4.71; R2 0.9923. So it can be concluded that UV-VIS spectroscopic fingerprint analysis with a combination of chemometrics can distinguish Combretum indicum Varr leaves. B against the occurrence of leaf adulteration of Combretum indicum Varr. M in the normal model with a wavelength of 296.09-261.64 nm.